Do the same chlorinated organophosphorus flame retardants that cause cytotoxicity and DNA damage share the same pathway? - Shengwu Yuan; Hong Zhang; Shuhang Wang; Xia Jiang; Mei Ma; Yiping Xu; Yingnan Han; Zijian Wang (Ecotoxicology and Environmental Safety, 2024)
Organophosphorus flame retardants (OPFRs) have been frequently detected with relatively high concentrations in various environmental media and are considered emerging environmental pollutants. However, their biological effect and underlying mechanism is still unclear, and whether chlorinated OPFRs (Cl-OPFRs) cause adverse outcomes with the same molecular initial events or share the same key events (KEs) remains unknown. In this study, in vitro bioassays were conducted to analyze the cytotoxicity, mitochondrial impairment, DNA damage and molecular mechanisms of two Cl-OPFRs. The results showed that these two Cl-OPFRs, which have similar structures, induced severe cellular and molecular damages via different underlying mechanisms. Both tris(2-chloroethyl) phosphate (TCEP) and tris(1-chloro-2-propyl) (TCPP) induced oxidative stress-mediated mitochondrial impairment and DNA damage, as shown by the overproduction of intracellular reactive oxygen species (ROS) and mitochondrial superoxide. Furthermore, the DNA damage caused by TCPP resulted in p53/p21-mediated cell cycle arrest, as evidenced by flow cytometry and real-time PCR. At the cellular and molecular levels, TCPP increased the sub-G1 apoptotic peak and upregulated the p53/Bax apoptosis pathway, possibly resulted in apoptosis associated with its stronger cytotoxicity. Although structurally similar to TCPP, TCEP did not induce mitochondrial impairment and DNA damage by the same KEs. These results provide insight into the toxicity of Cl-OPFRs with similar structures but different mechanisms, which is of great significance for constructing adverse outcome pathways or determining intermediate KEs.